2021
DOI: 10.3390/pharmaceutics13050712
|View full text |Cite
|
Sign up to set email alerts
|

Ferri–Liposomes: Preformulation and Selective Cytotoxicity against A549 Lung Cancer Cells

Abstract: Liposomes have become successful nanostructured systems used in clinical practices. These vesicles are able to carry important drug loadings with noteworthy stability. The aim of this work was to develop iron oxide-loaded stealth liposomes as a prospective alternative for the treatment of lung cancer. In this study, citric acid iron oxide nanoparticles (IONPs-Ac) were synthesized and encapsulated in stealth liposomes. Their cytotoxicity and selectivity against lung tumor cells were assessed. Stealth liposomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Graphical plotting of concentration vs. OD values was analyzed, and inhibition of proliferation by the extract was compared to vehicle-treated control. IC 50 values (concentration showing 50% proliferation inhibition) for carotenoid extract were calculated for both MCF-7 and MDA-MB-231 cells, and the extract was further evaluated in normal cells (HEK 293T) with corresponding IC 50 concentrations to check whether the anti-proliferative potency is restricted to cancer cell line only ( de Souza et al, 2021 ; Fatima et al, 2021 ; Kaur et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Graphical plotting of concentration vs. OD values was analyzed, and inhibition of proliferation by the extract was compared to vehicle-treated control. IC 50 values (concentration showing 50% proliferation inhibition) for carotenoid extract were calculated for both MCF-7 and MDA-MB-231 cells, and the extract was further evaluated in normal cells (HEK 293T) with corresponding IC 50 concentrations to check whether the anti-proliferative potency is restricted to cancer cell line only ( de Souza et al, 2021 ; Fatima et al, 2021 ; Kaur et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The p53 gene is an important tumor suppressor gene, and its mediated cell cycle inhibition, senescence, and apoptosis Frontiers in Genetics frontiersin.org play an important role in the occurrence and development of tumors (Coskun et al, 2022). Some recent studies have revealed that the relationship between the ferroptosis process and the TP53 gene, implying that the P53 protein may play a role in the regulation of the ferroptosis process (Blaber et al, 2015;Jiang et al, 2015;Chen et al, 2020;De Souza et al, 2021). However, the specific molecular mechanism of p53-regulated ferroptosis in preeclampsia still needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both ferroptosis and apoptosis were induced by targeting the mitochondrial membrane. [116] Iridium complexes are attracting attention as a potential alternative to cisplatin due to their lower toxicity, reduced adverse effects, improved water tolerance, ability to target mitochondria, and other favorable properties. [117,118] Liao et al developed iridium-loaded liposomes to achieve an apoptotic effect by targeting mitochondrial membranes, similar to the previous study.…”
Section: Hydrophilic and Hydrophobicmentioning
confidence: 99%